Representation of Children and Childhood in Russian Channel Information Programs - O S Logunova (Peoples' Friendship University of Russia (RUDN University), 2014)
The article is based on the secondary analysis of the results of the content analysis of the information programs of the major Russian TV channels. The context and tone of the topic of childhood mentioned in these programs are considered. The analysis reveals the trend of depressive and catastrophic coverage of the group.